High entropy alloys synthesized by mechanical alloying: A review - Yadav Y.K.; Shaz M.A.; Mukhopadhyay N.K.; Yadav T.P. (My University, 2025)
High entropy alloys (HEAs) have attracted an intense interest from scientists, researchers, academics and industrialists in the recent times because of their exceptional physical, functional and chemical properties, which are superior to those of conventional alloys. The vast number of scientific publications has eclipsed many synthesis and production techniques being adopted for HEAs. Although the production processes for traditional alloys are well-established, a closer look must be given to the various synthesis methods used for multicomponent alloys for industrial applications. This review paper will fill this vacuum by providing a thorough and comprehensive investigation into the production of quinary, senary and higher order alloy systems in HEAs via mechanical alloying/milling. The mechanical alloying is a non-equilibrium synthesis technique that combines elemental powders through high-energy ball milling and eventually nanostructured materials can be produced. The intrinsic mechanical alloying processes of plastic deformation, cold-welding and fracture causes the changes in the size, configuration, and dispersion of the particles. As a result, a uniformly sized, finely divided powder develops; giving rise to the materials the special qualities compared to traditionally alloyed materials. Mechanical alloying is established widely for the synthesis of HEAs and other advanced materials. Through the approaches of mechanical alloying, this review paper seeks to analyze and throw light on the synthesis of HEAs especially, providing insightful information on this process and its significance for developing complex HEAs. © 2025 The Authors